Investigação molecular e comportamental da estimulação transcraniana por corrente alternada em camundongos - Fernanda Donizete Rezende (2021)
In the last two decades, the use of neuromodulation techniques has become present in the treatment of neuropsychiatric disorders, such as major depression, anxiety, mood and personality disorders, substance abuse, Alzheimer's disease, and attention deficit hyperactivity disorder (ADHD). Among the non-invasive brain stimulations, transcranial electrical stimulations stand out, being widely used in humans for therapeutic purposes or in healthy individuals. Transcranial Alternating Current Stimulation (tACS) draws attention due to its characteristic electrical current with alternation between the poles, promoting a sinusoidal wave pattern that resembles the one of neuronal firings, enabling the mimicry of endogenous brain oscillations. Despite this, there is still not enough information to elucidate its action mechanisms. Therefore, further studies are needed, preferably in animal models. Our goal was to evaluate the effect of Transcranial Alternating Current Stimulation on the behavior and brain of C57Bl/J6 mice stimulated under sedation and in different protocols. Our results did not demonstrate positive or negative action of tACS. Considering our limitations and future perspectives for the use of transcranial alternating current stimulation, we suggest further study, especially with animal models, encephalography readings, and tACS protocols in animals awake while performing tasks.